On the all-inclusive society, or how to leave no one behind - Jannick Friis Christensen; Emil Falster; Barbara Carreras; Sofie Skoubo (Kvinder, Køn & Forskning)
This interview article brings together Dan Goodley, Yanki Lee, Jos Boys, and Sarah Glerup in conversation about an overall exploratory question of how we can create an inclusive society for all, taking the United Nations Sustainable Development Goals (SDG) and pledge to Leave No One Behind (LNOB) as point of departure. The panel embodies perspectives from different academic disciplines in disability studies and architectural design, but also knowledge based on lived experience from activist practices. In discussing themes of social inclusion, individualisation, methodology, representation, identity politics, normal space, disruption, and change; the panelists share their reflections on critical concepts such as neoliberal ableism, the super cripple, and equity tourism. Besides contributing with an interdisciplinary scholarly dialogue the article concludes by highlighting key insights from the interview on the relationship of contemporary societal and cultural disability issues in theory and practice.